Depressive symptoms and adverse outcomes from hospitalization in older adults: secondary outcomes of a trial of falls prevention education - Haines, T.; Williams, C.; Hill, A.; McPhail, S.; Hill, Keith; Brauer, S.; Hoffmann, T.; Etherton-Beer, C. (2015)
Depression is common in older people and symptoms of depression are known to substantially increase during hospitalization. There is little known about predictors of depressive symptoms in older adults or impact of common interventions during hospitalization. This study aimed to describe the magnitude of depressive symptoms, shift of depressive symptoms and the impact of the symptoms of depression among older hospital patients during hospital admission and identify whether exposure to falls prevention education affected symptoms of depression. Participants (n=1206) were older adults admitted within two Australian hospitals, the majority of participants completed the Geriatric Depression Scale - Short Form (GDS) at admission (n=1168). Participants' mean age was 74.7 (±SD 11) years and 47% (n=551) were male. At admission 53% (619 out of 1168) of participants had symptoms of clinical depression and symptoms remained at the same level at discharge for 55% (543 out of 987). Those exposed to the low intensity education program had higher GDS scores at discharge than those in the control group (low intensity vs control n=652, adjusted regression coefficient (95% CI)=0.24 (0.02, 0.45), p=0.03). The only factor other than admission level of depression that affected depressive symptoms change was if the participant was worried about falling. Older patients frequently present with symptoms of clinical depression on admission to hospital. Future research should consider these factors, whether these are modifiable and whether treatment may influence outcomes.